2017
DOI: 10.12659/msm.900471
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Extraction, Preliminary Characterization, and In Vitro Antioxidant Activity of Polysaccharides from Glycyrrhiza Uralensis Fisch

Abstract: BackgroundThis study performed optimized extraction, preliminary characterization, and in vitro antioxidant activities of polysaccharides from Glycyrrhiza uralensis Fisch.Material/MethodsThree parameters (extraction temperature, ratio of water to raw material, and extraction time) were optimized for yields of G. uralensis polysaccharides (GUP) using response surface methodology with Box-Behnken design (BBD). The GUP was purified using DEAE cellulose 32-column chromatography. The main fraction obtained from G. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…It has been reported that polysaccharides of G. uralensis have antioxidant activities [30,31,46]. Similarly, we also found that all three GUPS fractions have antioxidant activities.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It has been reported that polysaccharides of G. uralensis have antioxidant activities [30,31,46]. Similarly, we also found that all three GUPS fractions have antioxidant activities.…”
Section: Discussionsupporting
confidence: 86%
“…GUPS-I might be a neutral polysaccharide because it coeluted with distilled water, whereas both GUPS-II and GUPS-III, which eluted with NaCl solution, might be acidic polysaccharides [29]. The results are similar to previous studies which reported that three major fractions can be obtained from crude polysaccharides of G. uralensis [30,31], but different from another study which reported that five fractions can be observed [46].…”
Section: Discussionsupporting
confidence: 67%
“…DNA authentication, combined with chemometric analyses of major flavanones and chalcones, enabled the characterization of mixtures, hybrids, and species outliers (Simmler et al, ; Song et al, ). In pharmacological and clinical studies, Glycyrrhizae Radix et Rhizoma had several pharmacological properties including antioxidant, anti‐inflammatory, anticancer, and immunomodulatory properties (Chen, Li, & Gu, ; Hosseinzadeh & Nassiri‐Asl, ; Yang, Yuan, Ma, Zhou, & Liu, ). Glycyrrhetinic acid markedly upregulated the activities of the antioxidant enzymes and increased the content of skin collagen, whereas it obviously downregulated the expression of inflammatory cytokines in vitro (Kong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The most important action for licorice polysaccharides is the ability of the polysaccharides to enhance the anticancer cytokine IL-7, which is essential for the maturation and proliferation of immune cells and it is shown with good prognosis of cancer ( Ayeka et al 2016 ). Moreover, three purified licorice polysaccharides with lower molecular weight exhibited at the same concentration higher antioxidant activities ( Zhang et al, 2015 ; Chen et al, 2017 ).This antioxidant activity was highly enhanced by the selenylation modification of licorice polysaccharide ( Lian et al, 2018 ).…”
Section: Prevention Of Covid-19- Induced Autoimmune Diseases By Immunmentioning
confidence: 99%